Organization of creative activities of students: aims, methodology, outcomes - Dmitry A. Trischenko (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Creative activities of both students of Master’s and Bachelor’s degree programs refers increasingly to scientific creativeness although it is stated that training on Bachelor’s degree program is based on competence and practical-oriented approach carried out towards preparing professional workers required at the labor market rather than researchers. The government’s fostering actions promoting student creative contests are focused on identifying and supporting young talents primarily through all- Russian student Olympiads, which have recently been the most popular statesponsored form of competitions. Nevertheless, within the frames of the Russian educational system students’ creative contests are useful and productive not only to identify and support a limited amount of young talents but to improve the quality of training for much greater number of students. Therefore, the aim of this research is to substantiate that the forms of student creative contests would be more responsive to professional specifics of Bachelor training and perform an increasing range of functions: generating of enthusiasm for learning, developing competition skills and abilities to evaluate the competence level. Moreover, the governmental educational policies should be built upon previously established organizational forms of such contests. It is distinguished that the “Olympic movement” has definite drawbacks, which was evidently proved by the results of the Olympiad conducted for bachelor students of “Advertising and Public Relations” training area. Some all-Russian creative contests for students of media communications, design and adjacent specialties were briefly reviewed. The analysis of almost ten years of the author’s experience of creative activities organization of the students of “Advertising and Public Relations” training area studying at Belgorod University of Cooperation, Economics and Law allows to examine motivation, the forms of student association work, the outcomes of the student participation in various creative contests and to address such issues as the possibility of using contests’ outcomes as an assessment measure for a competence level. The author states the fairness of such evaluation approach. Additionally, the main and the supporting effects of the association’s activities are discovered and the basic methodological approaches to this form of student creativeness promotion are defined. The student creative association, which goal is to participate in all-Russian contests of professional skills is able to face a wide range of educational challenges. Furthermore, the logic of the practically-oriented approach suggests that the initiative in organization of creative contests should belong not to universities but to non-for-profit professional associations.